THE USE OF LANGUAGE LABORATORY TO TEACH LISTENING IN STATE SENIOR HIGH SCHOOLS IN SURABAYA (RETAIN, 2016)
THE USE OF LANGUAGE LABORATORY TO TEACH LISTENING IN STATE SENIOR HIGH SCHOOLS IN SURABAYA Ema Putri Yuwana English Education Study Program, English Language and Literature Department, Faculty of Languages and Arts, State University of Surabaya Email: emayuwana@mhs.unesa.ac.id Ahmad Munir English Education Study Program, English Language and Literature Department, Faculty of Languages and Arts, State University of Surabaya Email: ahmadmunir@unesa.ac.id Abstract This study investigates with the use of language laboratory to teach listening in all state senior high schools in Surabaya. The objectives of this study are to find out frequency of language laboratory in state senior high schools, the purposes of using it, and how English teachers in state senior high schools teach listening in language laboratory. A survey study was applied in this research. The population of this study were 22 state senior high schools in Surabaya. The data were obtained from questionnaires which had been filled by an English teacher from each school as a representative. Then, the data were analyzed quantitatively. This study found that the frequency of language laboratory use to teach listening was low, there were various purpose of using language laboratory used by English teachers in state senior high schools in Surabaya, yet the main purposes in most state senior high schools in Surabaya were to accomplish teaching of listening by giving practice and exercise and prepare CBT national examination, and almost all English teachers in state senior high schools in Surabaya followed main procedure in teaching listening, which are pre-listening, whilst listening, and post listening. They also applied top-down and bottom-up technique in listening. Keywords: Language laboratory, Listening, State Senior High Schools Abstrak Penelitian ini berkaitan dengan penggunaan laboratorium bahasa untuk pengajaran menyimak bahasa Inggris di seluruh SMA negeri di Surabaya. Tujuan dari penelitian ini adalah untuk mengetahui frekuensi penggunaan laboratorium bahasa di seluruh SMA negeri di Surabaya, tujuan penggunaan laboratorium bahasa, dan bagaimana guru mengajar menyimak menggunakan laboratorium bahasa. Studi survey diterapkan dalam penelitian ini. Populasi penelitian ini adalah 22 SMA negeri di Surabaya. Data penelitian diperoleh dari kuesioner yang telah diisi oleh salah satu guru dari masing-masing sekolah sebagai perwakilan. Kemudian, data diproses dan dianalisis secara kuantitatif. Penelitian ini menunjukkan frekuensi penggunaan laboratorium bahasa di seluruh SMA negeri di Surabaya rendah, ada berbagai tujuan penggunaan laboratorium bahasa, namun tujuan utamanya adalah untuk pengajaran menyimak bahasa Inggris melalui latihan-latihan dan persiapan UNBK, dan hampir seluruh guru bahasa Inggris di SMA negeri Surabaya mengikuti prosedur utama dalam pengajaran menyimak, yakni pre-listening, whilst listening, and post listening. Guru juga menerapkan top-down and bottom-up teknik dalam pengajaran listening. Kata Kunci: Laboratorium bahasa, Menyimak, SMA negeri